Creating Occupational Therapy: The Challenges to Defining a Profession. Issue 2 (3rd April 2018) - Reed, Kathlyn L.
ABSTRACT: The creation of a new profession in the early 20th century, such as occupational therapy, required a commitment to certain ideas and a willingness to accept certain challenges. This study examines the commitment to the idea of therapeutic and health supporting occupation by the early leaders and proponents of the profession and the challenges they faced in gaining acceptance of occupational therapy as a profession capable of delivering a valued health care service to society. Six challenges are reviewed as they occurred in the history of the profession and as they continue to challenge the profession into the present era.